Spiritual intelligence and teachers' intention to quit: the mechanism roles of sanctification of work and job satisfaction - Vem, Linus Jonathan; Ng, Imm Siew; Sambasivan, Murali; Kok, Tee Keng (Emerald Publishing Limited, 2024)
Purpose: The main objective of this study is to analyze the impact of spiritual intelligence (SI) based on its four dimensions (critical existential thinking (CET), personal meaning production (PMP), transcendental awareness (TA) and conscious state expansion (CSE)) on teachers' turnover intention (TI) through sanctification of work (SoW) and job satisfaction (JS). Design/methodology/approach: Drawing from multiple intelligence theory, this study adopted a cross-sectional design to explore the hypothesized relationships. Copies of the questionnaire were distributed to 367 teachers working in public schools in Plateau State, Nigeria, and 290 out of the retrieved copies were useable. The data collected were analyzed using variance-based structural equation modeling (SEM), Smart-PLS 4. Findings: The results suggest that SI does not significantly influence TI, while SoW and JS mediate the relationship between SI and TI. Practical implications: The result suggests that SoW and JS are significant mechanisms through which SI predicts teachers' TI. This highlights the need for educational policymakers to integrate spiritual literature as well as imbibe spiritual practices such as prayers, meditations and yoga either at work or privately to enhance the development of SI among teachers. Originality/value: The results offer an insightful understanding of SI and how it influences work outcomes. The mechanism roles of SoW and JS explain the process by which one's perceived numinous object, activity event and job experience influence a job decision.